Kepemimpinan Pastoral yang Autentik dalam Membentuk Spiritualitas Gen Z di Era Post-Truth: Kajian 1 Petrus 5:2–3 - Riska Aftur; Roni Kurniawan; Haryadi Sarjono (STTI Harvest Semarang, 2026)
Generation Z, who live in a massive flow of digital information that is often detached from objective truth. Pastoral leadership faces new demands to not only carry out the administrative functions of the church, but also to build real and tangible spiritual exemplarity and integrity. 1 Peter 5:2–3 offers a framework for pastoral leadership based on biblical truth, but its relevance to the spiritual formation of Gen Z in the post-truth era has not been systematically explored, especially given Gen Z's increasing scepticism towards spiritual leadership and their tendency to develop individual and digital spirituality. This study aims to analyse pastoral leadership and theology based on 1 Peter 5:2–3 in strengthening Gen Z spirituality in the post-truth era. A qualitative approach with biblical analysis and contextual pastoral theology studies was used. It can be concluded that a biblical study of 1 Peter 5:2–3 confirms that pastoral leadership based on willingness, integrity, and exemplary behaviour is a solid theological foundation for church ministry. Analysis of the characteristics of Gen Z spirituality in the post-truth era shows the need for a pastoral leadership model that is dialogical, authentic, and contextual in order to respond to the scepticism and digital dynamics of this generation. The integration of biblical principles with adaptive educational and pastoral ministry strategies has proven to be relevant in strengthening Gen Z spirituality and enriching the development of contemporary pastoral theology. AbstrakEra post-truth menghadirkan tantangan serius bagi pembentukan spiritualitas generasi Z yang hidup dalam masifnya arus informasi digital yang sering kali terlepas dari kebenaran objektif. Kepemimpinan gembala menghadapi tuntutan baru untuk tidak hanya menjalankan fungsi administratif gereja, tetapi juga membangun keteladanan dan integritas spiritual yang realita dan nyata. Teks 1 Petrus 5:2–3 menawarkan kerangka tentang kepemimpinan pastoral yang berlandaskan kebenaran alkitabiah, namun relevansinya bagi pembinaan spiritualitas Gen Z di era post-truth belum banyak dieksplorasi secara sistematis. apalagi meningkatnya skeptisisme generasi Z terhadap kepemimpinan rohani serta kecenderungan membangun spiritualitas yang bersifat individual dan digital. Penelitian ini bertujuan menganalisis kepemimpinan gembala dan teologi pastoral berdasarkan 1 Petrus 5:2–3 dalam memperkuat spiritualitas Gen Z di era post-truth. Pendekatan kualitatif dengan metode analisis biblika dan kajian teologi pastoral kontekstual. Maka dapat disimpulkan bahwa Kajian biblika terhadap 1 Petrus 5:2–3 menegaskan bahwa kepemimpinan gembala yang berlandaskan kerelaan, integritas, dan keteladanan merupakan fondasi teologis yang kokoh bagi pelayanan gereja. Analisis terhadap karakteristik spiritualitas Gen Z di era post-truth menunjukkan perlunya model kepemimpinan pastoral yang dialogis, autentik, dan kontekstual untuk menjawab skeptisisme serta dinamika digital generasi ini. Integrasi prinsip alkitabiah dengan strategi pendidikan dan pelayanan pastoral yang adaptif terbukti relevan dalam memperkuat spiritualitas Gen Z serta memperkaya pengembangan teologi pastoral kontemporer.